Direct visualization of current-induced spin accumulation in topological insulators - Yang Liu (Nature Portfolio, 2018)
Charge-to-spin conversion is a key theme of spintronics and its realization in topological materials is highly desired. Here, Liu et al. report spatial imaging of current-induced spin accumulation at the edges of Bi2Se3 and BiSbTeSe2 topological insulators.